Towards impressionism : landscape painting from Corot to Monet - Radzinowicz, David; Greub, Suzanne; Charles and Emma Frye Art Museum; George D. and Harriet W. Cornell Fine Arts Museum; Musée des beaux-arts (Reims, France) (Basel : Art Centre Basel ; Munich : Hirmer, 2017)
The Musée des Beaux-Arts, Reims owns the second largest collection of works by Jean-Baptiste Camille Corot after the Louvre, as well as excellent landscape paintings by artists of the Barbizon School. Corot was one of the most significant painters involved with the barbizonists. Studying the Reims holdings further, it seemed evident to edit a catalogue and curate an exhibition that reaches from the romantic spirit in French landscape painting to the School of Barbizon on to the group of artists around Eugène-Louis Boudin at Honfleur - the true cradle of Impressionism - and lastly to the impressionists Claude Monet, Camille Pissarro and Pierre-Auguste Renoir. Exhibition: Cornell Fine Arts Museum, Winter Park, USA (20.01.-08.04.2018) / Frye Art Museum, Seattle, USA (12.05.-05.08.2018).
The Romantic spirit of French landscape painting / Michael Clarke, former Director, Scottish National Gallery, Edinburgh -- Corot and the School of Barbizon / Michael Clarke, former Director, Scottish National Gallery, Edinburgh -- "The true cradle of Impressionism": Eugène Boudin, Claude Monet, and the School of Honfleur / Frances Fowle, Reader in History of Art, University of Edinburgh ; Senior Curator, Scottish National Gallery, Edinburgh.
Published on the occasion of an exhibition featuring works from the collection of the Musée des Beaux-Arts, Reims, held at the Cornell Fine Arts Museum, Rollins College, Winter Park, Florida, January 20 - April 8, 2018; Frye Art Museum, Seattle, Washington, May 5 - July 29, 2018.
Includes bibliographical references (pages 140-141).
Mode of access: Internet.
Keywords: Musée des beaux-arts (Reims, France); Musée des beaux-arts (Reims, France); Musée des beaux-arts (Reims, France); 1800-1899; Painting; Landscape painting, French; Impressionism (Art); Barbizon school; Exhibition catalogs; Painting -- France -- Exhibitions; Barbizon school -- Exhibitions; Impressionism (Art) -- France -- Exhibitions; Landscape painting, French -- Exhibitions -- 19th century; Peinture -- France -- Reims -- Expositions; École de Barbizon -- Expositions; Impressionnisme (Art) -- France -- Expositions; Peinture de paysages française -- 19e siècle -- Expositions; Painting -- France -- Reims -- Exhibitions; Barbizon school -- Exhibitions; Impressionism (Art) -- France -- Exhibitions; Landscape painting, French -- 19th century -- Exhibitions; France -- Reims; France; Exhibition catalogs